The Dickey-Fuller-test for exponential random walks - Laurie Davies; Walter Krämer (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2000)
We derive the probability limit of the standard Dickey-Fuller-test in the context of an exponential random walk. This result might be useful in interpreting tests for unit roots when the test is inadvertantly applied to the levels of the data when the true random walk is in the logs.
Keywords: 519; Unit Root Test; Theorie; Random Walk